Uptake and intracellular fate of biocompatible nanocarriers in cycling and noncycling cells. (22nd January 2019) - Costanzo, Manuela; Vurro, Federica; Cisterna, Barbara; Boschi, Federico; Marengo, Alessandro; Montanari, Elita; Meo, Chiara Di; Matricardi, Pietro; Berlier, Gloria; Stella, Barbara; Arpicco, Silvia; Malatesta, Manuela
Aim: To elucidate whether different cytokinetic features (i.e., presence or absence of mitotic activity) may influence cell uptake and distribution of nanocarriers, in vitro tests on liposomes, mesoporous silica nanoparticles, poly(lactide-co-glycolide) nanoparticles and nanohydrogels were carried out on C2C12 murine muscle cells either able to proliferate as myoblasts (cycling cells) or terminally differentiate into myotubes (noncycling cells).Materials & methods: Cell uptake and intracellular fate of liposomes, mesoporous silica nanoparticles, poly(lactide-co-glycolide) nanoparticles and nanohydrogels were investigated by confocal fluorescence microscopy and transmission electron microscopy.Results: Nanocarrier internalization and distribution were similar in myoblasts and myotubes; however, myotubes demonstrated a lower uptake capability.Conclusion: All nanocarriers proved to be suitably biocompatible for both myoblasts and myotubes. The lower uptake capability of myotubes is probably due to different plasma membrane composition related to the differentiation process.